1965
DOI: 10.1182/blood.v25.5.839.839
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Utilization of Iron by Scorbutic Guinea Pigs

Abstract: Administration of iron to guinea pigs during the progress of development of scurvy did not check the onset of anemia but enhanced it. Iron treatment also could not correct hypoferemia observed in the scorbutic condition although absorption of iron from the intestinal tract was not defective. The absorbed iron was deposited in tissues as hemosiderin. Ascorbic acid seems to be necessary for utilization of iron in the synthesis of hemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Influence of Ascorbic Acid and Vitamin E. Many workers have reported that ascorbic acid improves the absorption and utilization of iron (Apte and Venkatachalam, 1965;Banerjee and Chakrabarty, 1965;Brise and Hallberg, 1962;Greenberg et al, 1957;McCurdy and Dern, 1968). Brise and Hallberg (1962) showed that the effect was in the digestive tract, and that intravenous ascorbic acid had no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of Ascorbic Acid and Vitamin E. Many workers have reported that ascorbic acid improves the absorption and utilization of iron (Apte and Venkatachalam, 1965;Banerjee and Chakrabarty, 1965;Brise and Hallberg, 1962;Greenberg et al, 1957;McCurdy and Dern, 1968). Brise and Hallberg (1962) showed that the effect was in the digestive tract, and that intravenous ascorbic acid had no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Defective utilization of iron in scurvy is well known (9,10) and lack of response to iron administration during vitamin C deficiency has been reported in studies with experimental animals (10). Ascorbic acid has a key role in the absorption of dietary non‐heme iron (11), as the reduction of insoluble ferric iron to the more soluble ferrous iron is a critical step for mucosal cell iron uptake (12,13).…”
Section: Vitamin C‐associated Disorders In Dialysis Patientsmentioning
confidence: 99%
“…The tissue of scorbutic guinea pigs has increased deposits of hemosiderin, a storage form of iron with limited bioavailability, while the more readily utilized ferritin fraction of liver iron is decreased (10). Vitamin C can reverse this process; South African Bantu, who may suffer from dietary iron overload from use of iron‐containing cooking utensils, are able to mobilize storage iron following dietary vitamin C supplementation (16,17).…”
Section: Vitamin C‐associated Disorders In Dialysis Patientsmentioning
confidence: 99%